Content analysis of the current state of popularization of science and cultural heritage of Kazakh intellectuals (Journal of Philosophy Culture and Political Science, 2025)
The article reflects the results of the analysis of digital content, which revealed the legacy of Kazakh intellectuals in the first half of the twentieth century and the state of popularization of science. The purpose of the study is to determine the level of culture of popularization of science and intellectuals of Alash, to demonstrate the indicator of popularization using quantitative data.. There are no studies in cultural studies in Kazakhstan that would consider cultural phenomena using the content analysis method. Therefore, the results of the article are relevant in determining cultural changes in society. With the help of this method, the work of information sources forming public consciousness is clearly visible. The scientific value of the article As an experimental phenomenon of cultural development lies in the fact that the ability to appreciate intellectuals who lead, and the popularization of science in a broader sense, convincingly proves the balance of dissemination in society as everyday information. The results were able to show great differences between popular culture and intellectual culture. Popularization of the heritage of Kazakh intellectuals and discoveries in science in the information space is used to form systematic knowledge through the collection of digital data, to monitor the dynamics of cultural changes in society. The research data was obtained from domestic Internet sites. We show that the popularization of science and the heritage of Alash intellectuals, who brought independence closer, which was the common ideal of the Kazakh people, is an open question. Our research work will be continued through content analysis.Key words: Kazakh intellectuals of the twentieth century, Alash intelligentsia, science, education, culture of popularization.